Dimensi Sosial Ekonomi Bahari Usaha Perikanan Darat di Bungoro, Pangkajene dan Kepulauan - Rifal (Jurnal Ekonomi dan Riset Pembangunan, 2024)
This study aims to determine the socio-economic dimensions of inland fisheries in Bungoro, Pangkajene and Islands. Which examines the role of geographical location, demographics, and social conditions in organizing the socio-cultural dimensions of maritime in the area. To achieve this goal, a qualitative research method was adopted by means of observation, interviews, and documentation. The data obtained were then analyzed and interpreted based on relevant theories and research results. The results of this research show that the social dimension in the study of maritime culture is important to be highlighted. To see various social perspectives, it is seen from the study of maritime culture. In this case, it examines geographical, demographic and social conditions. Inland fisheries in Bungoro sub-district, Pangkajene and Islands (Pangkep) district, play an important role in the local economy, especially in rural areas. With its diverse geography, Bungoro has great potential to develop inland fisheries. Demographically, the region provides ideal land for fish farming ponds and ponds. Freshwater ponds are used to cultivate fish such as tilapia, catfish, milkfish, as well as several other types of freshwater fish.